JCMM 2023
DOI: 10.57159/gadl.jcmm.2.1.23032
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Hofstede’s Cultural Dimensions for Devising COVID-19 Control Strategies

Abstract: The COVID-19 Pandemic has caused unprecedented global challenges, including significant socioeconomic disruptions and the closure of schools and universities in almost all countries. Understanding the role of culture in shaping individual and societal responses to the Pandemic is crucial. This review article examines the applicability of Hofstede's cultural dimensions framework in devising effective COVID-19 control strategies. The article provides an overview of each dimension and its impact on the implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…Some scholars have analyzed the gap between different national cultures from the dimensions of individualism/collectivism and uncertainty avoidance in Hofstede’s national cultural perspective [ 5 , 13 , 16 , 23 , 24 ]. Meanwhile, Shetty et al [ 14 ] studied an overview of five of Hofstede’s dimensions (PDI, IDV, MAS, UAI, and LTO) and their impact on the implementation of COVID-19 control strategies. Timo et al [ 15 ] studied the correlation between Hofstede’s six cultural dimensions, COVID-19 data, and the role of socio-economic factors drawn after the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Some scholars have analyzed the gap between different national cultures from the dimensions of individualism/collectivism and uncertainty avoidance in Hofstede’s national cultural perspective [ 5 , 13 , 16 , 23 , 24 ]. Meanwhile, Shetty et al [ 14 ] studied an overview of five of Hofstede’s dimensions (PDI, IDV, MAS, UAI, and LTO) and their impact on the implementation of COVID-19 control strategies. Timo et al [ 15 ] studied the correlation between Hofstede’s six cultural dimensions, COVID-19 data, and the role of socio-economic factors drawn after the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the above studies related to the COVID-19 pandemic and culture mostly focus on the dimensions of individualism/collectivism and uncertainty avoidance of Hofstede’s national cultural theory perspective. Meanwhile, Shetty et al [ 14 ] has studied an overview of five of Hofstede’s dimensions (PDI, IDV, MAS, UAI, and LTO) and their impact on the implementation of COVID-19 control strategies. Their study used a case analysis of four countries: India, the United Kingdom, the United States of America, and Poland, to illustrate the interplay between culture and COVID-19 control strategies, and they demonstrated that cultural differences can significantly impact the success of COVID-19 control strategies [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations